FUNGSI KOMUNIKASI ANTAR PRIBADI ANTARA KONSELOR DENGAN DAMPINGAN PADA UPAYA PENANGANAN KORBAN PENELANTARAN RUMAH TANGGA (Studi Kasus di Lembaga Sosial Masyarakat (Lsm) SAPUAN (Sahabat Perempuan Dan Anak) Blitar) - Andiwi Meifilina (Universitas Islam Balitar, 2017)
The problem that is encountered is there are still victims who have difficulty in terms of communication with the counselor. This is indicated by the number of assistants who are still afraid, passive, emotional and crying in complaining. Seeing this problem, interpersonal communication is very important to be owned by the victims because the beneficiaries are expected to communicate well in solving and to convey the problem to the counselor. The type of approach chosen in this research is descriptive qualitative study about interpersonal communication function between counselor and household neglect victim at LSM (Non-Governmental Organization) of SAPUAN (Friends of Woman and Children) Blitar.Research on the interpersonal communication function between counselor and assistant to the effort of handling victim neglect of household in non-governmental organization LSM (Friends of girl and child) Blitar using qualitative descriptive method. With this type of case study approach.And the interpersonal communication function between the counselor and the victim on the effort of handling the neglected victim of the household in LSM is very important because it involves the relationship between the victim with the counselor and the interpersonal communication relationship must go well so that there is no gap or distance between counselor and victim. And the interpersonal communication function that exist in non-governmental organizations LSM SAPUAN (Friends of women and children), namely: Interpersonal communication helps the development of intellectual and social, Identity or our identity formed in and through communication with others, In order to understand the reality around us and testing the truths of the impressions we have about the world around us, we need to compare with the impressions and perceptions we have about the world around us, we need to compare them with the impressions and understandings of others and the reality Similarly, our mental health is largely determined by the quality of our communication or relationships with others, especially those who are significant figures in our lives.